Culture, context, and ethics in the therapeutic use of hallucinogens: Psychedelics as active super-placebos?. (October 2022) - Dupuis, David; Veissière, Samuel
Following decades of prohibition and widespread concern about their mind-altering properties, there is increasing public, scholarly, and clinical interest in the therapeutic potential of psychedelic substances. Serotonergic substances in particular (DMT, psilocybin, and LSD) are now being tested as treatments for such ailments as depression, anxiety, and substance use disorder. This thematic issue of Transcultural Psychiatry presents articles that investigate the cultural assumptions, political dimensions, and clinical and ethical implications that arise from this renewed interest. After reviewing ongoing debates on therapeutic mechanisms of action and the importance of context, we argue that psychedelics can be conceptualized as "active super-placebos"—that is, substances that enhance ritual, symbolic, and interpersonal therapeutic processes by increasing suggestibility and the influence of extra-pharmacological, "non-specific" factors. Rather than simply freeing up habitual constraints on perception, the articles in this issue support the claim that psychedelic encounters typically entail processes of sense-making, crystallization of meaning, and enculturation into contextually mediated assumptive worlds (or ideologies) and behaviours that necessarily install novel constraints with potentially maladaptive consequences. We highlight the importance of clinical and epistemic integrity in the framing of psychedelic therapies. The importance of structuring and providing oversight for the therapeutic context raises difficult questions about the search for appropriate forms of epistemic authority that are at once respectful of the plural cultural origins of psychedelic rituals and mindful of best practices and standards in clinical care.